The hidden curriculum in under graduate medical education in Bangladesh: medical students' perception (Bangladesh Journal of Medical Education, 2017)
This descriptive cross sectional study was conducted among 386 students of 3rd phase of selected 2 government and 2 non government medical colleges of Bangladesh in 2013. The objective of the study was to find out the perceptions of the students regarding hidden curriculum in undergraduate medical education. Sampling technique was convenient. A self administered structured questionnaire was used and it consisting of 43 items in relation to hidden curriculum in the likert scale. Perceptions of the respondents were positive about 27 items that is the issues on these item areas were satisfactory in their institutes. Mean scores of these items were more than 3 for each. On the contrary perceptions of the respondents were negative for 16 items that is the issues on these item areas were not satisfactory in their institutes. Mean scores of these items were less than 3 for each. The study result can be used to sensitize and aware the concerned teachers/ authorities for valuing the importance of hidden curriculum and address the issues accordingly.Bangladesh Journal of Medical Education Vol.4(1) 2013: 20-24